The Influence of Service Quality, Business Capacity Development Programs, and Word of Mouth on Customer Satisfaction and Loyalty of Mekaar Permodalan Nasional Madani Customers in Bandung Branch - Neneng Yani; Siti Safaria (PT FORMOSA CENDEKIA GLOBAL, 2023)
To improve service quality, PNM innovated by launching the Business Capacity Development (PKU) program. PNM also empowers existing customers to attract new prospective customers through Word of Mouth. There are two analysis methods used, namely outer model analysis with Convergent Validity, Discriminant Validity, Composite Reliability, Cronbach's Alpha and using inner model analysis with Hypothesis Test. Outcome from this study are Customer Satisfaction affecting Customer Loyalty. Service positively and insignificant affecting on Customer Loyalty. The PKU program not affecting Customer Loyalty. WOM positively and insignificant affecting on Customer Loyalty. Service quality affecting customer satisfaction. PKU program not affecting customer satisfaction. WOM has a significant positive effect on Customer Satisfaction